Preparation method and application of fluorine-free sand streak agent
Through low-temperature plasma technology and microchannel reactor technology, a fluorine-free sand marking agent with surface grafting acrylic acid was prepared, which solved the potential risks of traditional fluorine-containing sand marking agents to the environment and health, and achieved more environmentally friendly and efficient sand Texture effect.
Patent Information
- Application Number
- CN202411712431.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sandwich agents contain fluorine, which poses potential risks to the environment and human health, and it is difficult to meet the environmental protection requirements of the modern coating industry.
The surface of PMMA micropowder is activated by low-temperature plasma technology, and graft copolymerization is carried out through a microchannel reactor to prepare a fluorine-free sandwich agent with surface grafting acrylic acid, combined with alcohol dispersants, and enhance PMMA micropowder in the coating. dispersion and sand texture effect.
The preparation of fluorine-free sand marking agent is realized, with better environmental protection and surface performance, and is suitable for a variety of industrial fields, reducing production costs and improving production efficiency.
Smart Images

Figure BDA0005156096800000121 
Figure BDA0005156096800000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a preparation method and application of a fluorine-free sand graining agent. Background Art
[0002] The preparation principle of sand-textured powder coating is to utilize the changes in the melt viscosity, surface tension and curing rate of the powder coating during baking and curing to cause the shrinkage of the coating surface. There are several general methods for forming sand texture: adding fillers, adding incompatible substances, adding rheological additives, and adding sand texture agents.
[0003] Adding sand graining agents is a conventional method of forming sand grains, but the most common sand graining agents are fluorine-containing sand graining agents. However, fluorine-containing sand graining agents contain fluorine elements, which may pose potential risks to the environment and human health in the context of increasingly stringent environmental regulations. Fluorine-free sand graining agents have more obvious environmental advantages compared to traditional fluorine-containing sand graining agents. Since they do not contain fluorine elements, fluorine-free sand graining agents are more in line with the environmental protection requirements of the modern coatings industry. Summary of the invention
[0004] The invention provides a preparation method of a fluorine-free sand graining agent and application thereof to replace the existing fluorine-containing sand graining agent.
[0005] The present invention provides a method for preparing a fluorine-free sand graining agent, comprising the following steps:
[0006] S11: Activate the surface of PMMA powder using low-temperature plasma technology;
[0007] S12: dispersing the activated PMMA powder in an organic solvent to obtain a reaction solution A; dispersing the acrylic acid monomer in an organic solvent to obtain a reaction solution B; and dispersing the initiator in an organic solvent to obtain a reaction solution C;
[0008] S13: Under nitrogen protection, the reaction liquid A, the reaction liquid B and the reaction liquid C are introduced into a microchannel reactor for graft copolymerization, and then washed and dried to obtain the PMMA micropowder with acrylic acid grafted on the surface.
[0009] Furthermore, the organic solvent is selected from any one of chloroform, dichloromethane, n-hexane, and tetrahydrofuran; and the initiator is selected from any one of ammonium persulfate and azobisisobutyronitrile.
[0010] Furthermore, in step S11, the particle size of the PMMA powder is 10 μm-50 μm.
[0011] Further, the flow rate of the reaction solution A is controlled to be 1-2 mL / min, and the mass fraction of the activated PMMA powder in the reaction solution A is 1-5%; and / or
[0012] The flow rate of the reaction solution B is controlled to be 0.9-2.2 mL / min, and the mass fraction of the acrylic acid monomer in the reaction solution B is 15-17%; and / or
[0013] The flow rate of the reaction liquid C is controlled to be 0.9-2.2 mL / min, and the mass fraction of the initiator in the reaction liquid C is 0.13-0.17%.
[0014] Furthermore, in step S13, the reaction temperature of the microchannel reactor is controlled to be 60-70°C.
[0015] The present invention also provides a sand-texture powder coating, the raw materials of which include, by weight: 80-100 parts of a resin base material; 2.5-3 parts of a fluorine-free sand-texture agent; 6-10 parts of an alcohol dispersant; and 5-12 parts of a curing agent.
[0016] Furthermore, the resin base material is selected from at least one of acrylic resin, polyurethane resin, epoxy resin and polyester resin.
[0017] Furthermore, the alcohol dispersant is selected from at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, pentanol, hexanol, and cyclohexanol.
[0018] The present invention also provides a method for preparing a sand-textured powder coating, comprising the following steps:
[0019] S21: obtaining a resin base material, a fluorine-free sand graining agent, an alcohol dispersant, and a curing agent according to their mass, and mixing and crushing them to obtain a premix;
[0020] S22: Extruding the premix through a twin-screw extruder, wherein the heating temperature of the twin-screw extruder is controlled at 80-120° C., and then cooling, tableting, crushing and grinding are performed in sequence to obtain a sand-textured powder coating, wherein the equivalent particle size D50 of the sand-textured powder coating is 20-45 μm.
[0021] The application also includes a workpiece, the surface of which is sprayed with the sand-textured powder coating.
[0022] In the technical solution of the present invention, the resin base material is used to improve the adhesion, weather resistance and mechanical properties of the coating to meet different application requirements. In order to improve the dispersion of PMMA powder in the coating, acrylic acid is grafted on its surface, and an alcohol dispersant is used to improve the uniformity of PMMA powder in the powder coating. The carboxyl group in acrylic acid and the hydroxyl group in the alcohol dispersant can form hydrogen bonds. During the preparation of the mixed material, the dispersion of PMMA powder can be improved due to the effect of hydrogen bonds; thus, the sand grain effect is better. Through an appropriate amount of curing agent, the hardness and chemical resistance of the coating are improved, and the service life is extended. The present invention has a good sand grain effect on the coating surface through a specific sand grain filler design, which improves the aesthetics; it can be widely used in casting, automobile manufacturing, machinery manufacturing and other fields to meet various industrial needs.
[0023] After adopting the technical solution of the present invention, at least one of the following technical effects is achieved:
[0024] 1. Environmental protection: The fluorine-free sand graining agent of the present invention does not contain harmful fluorides, meets environmental protection requirements, and reduces the impact on the environment.
[0025] 2. Excellent surface properties: When the fluorine-free sand graining agent of the present invention is applied to powder coatings, the coating surface has a good sand graining effect, thereby improving the aesthetics.
[0026] 3. Multifunctionality: The sand-textured powder coating of the present invention can be widely used in the fields of casting, automobile manufacturing, machinery manufacturing, etc., and can meet various industrial needs.
[0027] 4. Improve production efficiency: The formulation and process optimization of the sand-textured powder coating of the present invention make the production process more efficient and reduce production costs. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Fluorine-free sand graining agents not only have many advantages in environmental protection and economy, but also have broad application prospects. The ultimate goal is to reduce the impact on the environment while meeting the needs of the industry and achieve the goal of green casting. In sand grain coatings, the texture of sand grains can be formed in the following ways, such as using fillers with high oil absorption. Their oil absorption in the coating will prevent the resin from completely wrapping these filler particles; due to the insufficient amount of resin, the gaps between the filler particles are not completely filled, thus forming a rough and granular surface texture, that is, the sand grain effect. Another example is the addition of sand graining agents. Sand graining agents are usually some chemicals with low surface tension. After being added to the coating, these substances will be dispersed on the surface of the coating. Since the surface tension of the sand graining agent is lower than that of the base resin, when the coating is melted and leveled, the resin will "wrap" the sand graining agent, forming local tension unevenness.
[0030] The fluorine-free sand graining agent of the present invention is different from the above two types. It introduces a PMMA particle that is incompatible with the resin base material. During the curing process of the coating, the resin base material continues to harden into a film, while the PMMA particles fail to completely fuse with the base resin and remain on the surface of the film or inside the film to form a unique structure. The local inhomogeneity of these PMMA particles will cause the surface to present a sand grain-like texture. Due to the different sizes, distributions and types of polymers of the particles, the effects of these textures may vary, and may appear as a rough sandy surface or a fine particle distribution. Further, in order to improve the dispersion of PMMA powder in the coating, acrylic acid is grafted on its surface, and an alcohol dispersant is used to improve the uniformity of PMMA powder in the powder coating. The carboxyl group in acrylic acid and the hydroxyl group in the alcohol dispersant can form hydrogen bonds. During the preparation of the mixed material, the dispersion of PMMA powder can be improved due to the action of hydrogen bonds; thus, the sand grain effect is better.
[0031] Specifically, the present invention provides a fluorine-free sand graining agent for sand grain powder coating, wherein the raw materials thereof include, by mass: 80-100 parts of resin base material; 2.5-3 parts of fluorine-free sand graining agent; 6-10 parts of alcohol dispersant; and 5-12 parts of curing agent; wherein the fluorine-free sand graining agent is PMMA micropowder with surface grafted acrylic acid.
[0032] Further, the resin base material is selected from at least one of acrylic resin, polyurethane resin, epoxy resin, and polyester resin; and / or the alcohol dispersant is selected from at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, pentanol, hexanol, and cyclohexanol. Among them, the resin base material is preferably acrylic resin; the alcohol dispersant is preferably n-butanol. In a specific embodiment, those skilled in the art may also choose to add other additives according to actual needs, which will not be elaborated here.
[0033] Furthermore, PMMA micropowder with acrylic acid grafted on the surface is prepared by the following method:
[0034] S11: Activate the surface of PMMA powder using low-temperature plasma technology;
[0035] S12: dispersing the activated PMMA powder in an organic solvent to obtain a reaction solution A; dispersing the acrylic acid monomer in an organic solvent to obtain a reaction solution B; and dispersing the initiator in an organic solvent to obtain a reaction solution C;
[0036] S13: Under nitrogen protection, the reaction liquid A, the reaction liquid B and the reaction liquid C are introduced into a microchannel reactor for graft copolymerization, and then washed and dried to obtain PMMA micropowder with acrylic acid grafted on the surface.
[0037] Furthermore, the organic solvent is selected from any one of chloroform, dichloromethane, n-hexane, and tetrahydrofuran; and / or the initiator is selected from any one of ammonium persulfate and azobisisobutyronitrile.
[0038] Furthermore, in step S11, the particle size of the PMMA powder is 10 μm-50 μm.
[0039] In this embodiment, the surface of PMMA micropowder is first activated by low-temperature plasma treatment; the molecular separation of electron collision and photochemical action will produce plasma containing high-density free radicals, which can cause the chemical bonds on the surface of the material to break, thereby forming new functional groups such as hydroxyl (-OH), aldehyde (-COH) and carboxyl (-COOH) on the surface of the material. These functional groups can improve the wettability of PMMA micropowder and facilitate the grafting of molecules. The grafting treatment uses a microchannel reactor as a reaction site. The microchannel structure provides a large surface area, which helps to increase the reaction rate; at the same time, the microchannel reactor can achieve rapid heat transfer and mass transfer due to its small volume and large surface area, reducing the reaction time; its flow state can be precisely controlled, which is convenient for adjusting the reaction conditions.
[0040] In a specific embodiment, the particle size of PMMA powder is 40-50 μm; the reaction channel of the microchannel reactor is 200-300 μm; therefore, in order to achieve grafting of acrylic acid, it is very important to control the concentration and flow rate of the reaction solution.
[0041] Further, the flow rate of reaction liquid A is controlled to be 1-2 ml / min, and the mass fraction of activated PMMA powder in reaction liquid A is 1-5%; and / or the flow rate of reaction liquid B is controlled to be 0.9-2.2 ml / min, and the mass fraction of acrylic acid monomer in reaction liquid B is 15-17%; and / or the flow rate of reaction liquid C is controlled to be 0.9-2.2 ml / min, and the mass fraction of initiator in reaction liquid C is 0.13-0.17%.
[0042] Among them, in the reaction liquid A, the concentration of the activated PMMA powder is very low, because PMMA is a solid powder, in order to avoid channel clogging, its mass fraction is controlled at 1-5%, so the entire grafting reaction is carried out at a lower concentration, which is conducive to controlling the grafting effect of acrylic acid. For the grafting amount of acrylic acid monomer, the concentration and flow rate of the reaction liquid B can be controlled. Preferably, in the reaction liquid B, the mass fraction of acrylic acid monomer is 15-17%, and the flow rate of the reaction liquid B is 0.9-2.2 ml / min.
[0043] Furthermore, in step S13, the reaction temperature of the microchannel reactor is controlled to be 60-70°C.
[0044] Conventional autoclave reactions require the temperature to be controlled at 70-80°C; in this embodiment, due to the use of a microchannel reactor, the reaction rate and heat transfer are significantly improved, and the reaction temperature only needs to be controlled at 60-70°C; preferably 63-65°C.
[0045] Furthermore, PMMA micropowder is a composite micropowder of PMMA and nano-silicon dioxide, which can improve the wear resistance of the coating. The preparation process of the composite micropowder includes the following steps:
[0046] A: According to the mass fraction, 100 parts of methyl methacrylate, 20-30 parts of dispersant, and 8-10 parts of initiator are mixed to obtain an oil phase mixture;
[0047] B: According to the mass fraction, 100-120 parts of deionized water and 12-17 parts of stabilizer are mixed to obtain an aqueous phase mixture;
[0048] C: mixing the oil phase mixture and the water phase mixture, emulsifying and dispersing to obtain a reaction solution;
[0049] D: Add 25-30 parts of nano-silicon dioxide to the reaction solution; heat to 80-120°C while performing ultrasonic dispersion, and react for 8-12 hours to obtain a composite emulsion;
[0050] E: The composite emulsion is washed and dried in sequence to obtain composite micropowder of PMMA micropowder and nano-silicon dioxide.
[0051] The initiator is benzoyl peroxide; the dispersant is polymethylsiloxane; and the stabilizer is a mixture of polyvinyl alcohol and polyvinyl pyrrolidone (mass ratio 1:1).
[0052] The ultrasonic frequency of ultrasonic dispersion is 320-350kHz, and the ultrasonic power is 1.2-1.5kW.
[0053] In this embodiment, a dispersant and a stabilizer are introduced to form PMMA micropowder with a stable particle size. In the reaction liquid, the oil phase and the aqueous phase are emulsified and dispersed, and the oil phase exists in the form of small droplets. However, as the reaction proceeds, the small droplets of the oil phase may aggregate, thereby affecting the particle size of the final PMMA particles. Therefore, a stabilizer is added while maintaining an ultrasonic dispersion operation during the reaction to protect the stability of the oil phase droplets. Preferably, the stabilizer is a mixture of polyvinyl alcohol and polyvinyl pyrrolidone (mass ratio 1:1). The dispersant is selected as polymethylsiloxane, whose main chain can adsorb droplets of the oil phase, and the methyl groups on the side chains extend outward in the shape of comb teeth, which can act as a barrier, so that the droplets of the oil phase are separated from each other, thereby achieving control of the particle size of the PMMA micropowder.
[0054] In order to improve the wear resistance of PMMA micropowder, nano-silicon dioxide was introduced into the reaction solution. Ultrasonic dispersion can also maintain the dispersion of nano-silicon dioxide. Then, the solution was heated to the reaction temperature. As the polymerization reaction proceeded, nano-silicon dioxide was embedded in the interior of the PMMA micropowder, thereby preparing a composite micropowder of PMMA and nano-silicon dioxide.
[0055] The present invention also provides a method for preparing the sand-textured powder coating, comprising the following steps:
[0056] S21: obtaining a resin base material, a sand grain filler, an alcohol dispersant, and a curing agent according to their mass, and mixing and crushing them to obtain a premix;
[0057] S22: The premix is extruded through a twin-screw extruder, and then cooled, tableted, crushed and ground in sequence to obtain a sand-textured powder coating.
[0058] Further, the heating temperature of the twin-screw extruder is controlled at 80-120° C.; and / or the equivalent particle size D50 of the sand-textured powder coating is 30-50 μm.
[0059] Example 1
[0060] The present embodiment provides a sand-textured powder coating, wherein the raw materials include, by mass: 100 parts of a resin base material; 3 parts of a fluorine-free sand-texturing agent; 10 parts of an alcohol dispersant; and 12 parts of a curing agent. The fluorine-free sand-texturing agent is a PMMA micropowder with acrylic acid grafted on the surface; the resin base material is an acrylic resin; and the alcohol dispersant is n-butanol.
[0061] The present invention also provides a method for preparing the sand grain powder, comprising the following steps:
[0062] S21: Obtain resin base material, sand grain filler, alcohol dispersant, and curing agent according to mass, mix and crush them to obtain a premix.
[0063] S22: The premix is extruded through a twin-screw extruder, and then cooled, pressed, crushed and ground in sequence to obtain a sand-textured powder coating. The heating temperature of the twin-screw extruder is controlled at 120° C. The equivalent particle size D50 of the sand-textured powder coating screened out is 20-45 μm.
[0064] Wherein, the fluorine-free sand graining agent is prepared by the following method:
[0065] S11: Activate the surface of PMMA powder using low-temperature plasma technology.
[0066] S12: Dispersing the activated PMMA powder in an organic solvent to obtain a reaction solution A, wherein the mass fraction of the activated PMMA powder is 5%. Dispersing the acrylic acid monomer in an organic solvent to obtain a reaction solution B, wherein the mass fraction of the acrylic acid monomer is 17%. Dispersing the initiator in an organic solvent to obtain a reaction solution C, wherein the mass fraction of the initiator is 0.17%. The organic solvent is n-hexane, and the initiator is azobisisobutyronitrile.
[0067] S13: Under nitrogen protection, the reaction temperature of the microchannel reactor is controlled to 65°C, and reaction liquid A, reaction liquid B and reaction liquid C are introduced into the microchannel reactor for graft copolymerization. The flow rate of reaction liquid A is controlled to 2 ml / min, the flow rate of reaction liquid B is controlled to 2.2 ml / min, and the flow rate of reaction liquid C is controlled to 2.2 ml / min.
[0068] After the reaction is completed, the PMMA powder with acrylic acid grafted on the surface is obtained by washing and drying.
[0069] Example 2
[0070] The present embodiment provides a sand-textured powder coating, and the raw materials include, by mass: 80 parts of a resin base material; 2.5 parts of a fluorine-free sand-texturing agent; 6 parts of an alcohol dispersant; and 5 parts of a curing agent. The fluorine-free sand-texturing agent is a PMMA micropowder with acrylic acid grafted on the surface; the resin base material is an epoxy resin; and the alcohol dispersant is pentanol.
[0071] The present invention also provides a method for preparing the sand grain powder, comprising the following steps:
[0072] S21: Obtain resin base material, sand grain filler, alcohol dispersant, and curing agent according to mass, mix and crush them to obtain a premix.
[0073] S22: The premix is extruded through a twin-screw extruder, and then cooled, pressed, crushed and ground in sequence to obtain a sand-textured powder. The heating temperature of the twin-screw extruder is controlled at 80° C. The equivalent particle size D50 of the screened sand-textured powder is 20-45 μm.
[0074] Wherein, the fluorine-free sand graining agent is prepared by the following method:
[0075] S11: Activate the surface of PMMA powder using low-temperature plasma technology.
[0076] S12: Dispersing the activated PMMA powder in an organic solvent to obtain a reaction solution A, wherein the mass fraction of the activated PMMA powder is 1%. Dispersing the acrylic acid monomer in an organic solvent to obtain a reaction solution B, wherein the mass fraction of the acrylic acid monomer is 15%. Dispersing the initiator in an organic solvent to obtain a reaction solution C, wherein the mass fraction of the initiator is 0.13%. The organic solvent is dichloromethane, and the initiator is azobisisobutyronitrile.
[0077] S13: Under nitrogen protection, the reaction temperature of the microchannel reactor is controlled to 60°C, and reaction liquid A, reaction liquid B and reaction liquid C are introduced into the microchannel reactor for graft copolymerization. The flow rate of reaction liquid A is controlled to 1 ml / min, the flow rate of reaction liquid B is controlled to 0.9 ml / min, and the flow rate of reaction liquid C is controlled to 0.9 ml / min.
[0078] After the reaction is completed, the PMMA powder with acrylic acid grafted on the surface is obtained by washing and drying.
[0079] Example 3
[0080] The present embodiment provides a sand-textured powder coating, wherein the raw materials include, by mass: 90 parts of a resin base material; 2.7 parts of a fluorine-free sand-texturing agent; 8 parts of an alcohol dispersant; and 7 parts of a curing agent. The fluorine-free sand-texturing agent is a PMMA micropowder with acrylic acid grafted on the surface, the resin base material is an acrylic resin, and the alcohol dispersant is isopropyl alcohol.
[0081] The present invention also provides a method for preparing the sand grain powder, comprising the following steps:
[0082] S21: Obtain resin base material, sand grain filler, alcohol dispersant, and curing agent according to mass, mix and crush them to obtain a premix.
[0083] S22: The premix is extruded through a twin-screw extruder, and then cooled, tableted, crushed and ground to obtain a sand-textured powder. The heating temperature of the twin-screw extruder is controlled at 90° C. The equivalent particle size D50 of the screened sand-textured powder is 20-45 μm.
[0084] Wherein, the fluorine-free sand graining agent is prepared by the following method:
[0085] S11: Activate the surface of PMMA powder using low-temperature plasma technology.
[0086] S12: Dispersing the activated PMMA powder in an organic solvent to obtain a reaction solution A, wherein the mass fraction of the activated PMMA powder is 3%. Dispersing the acrylic acid monomer in an organic solvent to obtain a reaction solution B, wherein the mass fraction of the acrylic acid monomer is 16%. Dispersing the initiator in an organic solvent to obtain a reaction solution C, wherein the mass fraction of the initiator is 0.15%. The organic solvent is chloroform, and the initiator is ammonium persulfate.
[0087] S13: Under nitrogen protection, the reaction temperature of the microchannel reactor is controlled to 68°C, and reaction liquid A, reaction liquid B and reaction liquid C are introduced into the microchannel reactor for graft copolymerization. The flow rate of reaction liquid A is controlled to 1.5 ml / min, the flow rate of reaction liquid B is controlled to 1.8 ml / min, and the flow rate of reaction liquid C is controlled to 2.0 ml / min.
[0088] After the reaction is completed, the PMMA powder with acrylic acid grafted on the surface is obtained by washing and drying.
[0089] Example 4
[0090] This embodiment provides a sand-textured powder coating. The raw material ratio and preparation process are the same as those in Embodiment 1, except that the fluorine-free sand-textured agent is a composite micropowder of PMMA and nano-silicon dioxide.
[0091] The preparation process of composite micropowder includes the following steps:
[0092] A: According to mass, 100 parts of methyl methacrylate, 25 parts of dispersant, and 9 parts of initiator are mixed to obtain an oil phase mixture;
[0093] B: According to mass fraction, 11 parts of deionized water and 15 parts of stabilizer are mixed to obtain an aqueous phase mixture;
[0094] C: mixing the oil phase mixture and the water phase mixture, emulsifying and dispersing to obtain a reaction solution;
[0095] D: Add 27 parts of nano-silicon dioxide to the reaction solution; heat to 90°C while performing ultrasonic dispersion, and react for 9 hours to obtain a composite emulsion;
[0096] E: The composite emulsion is washed and dried in sequence to obtain composite micropowder of nano-silicon dioxide.
[0097] The initiator is benzoyl peroxide; the dispersant is polymethylsiloxane; and the stabilizer is a mixture of polyvinyl alcohol and polyvinyl pyrrolidone (mass ratio 1:1).
[0098] The ultrasonic frequency of ultrasonic dispersion is 340 kHz, and the ultrasonic power is 1.3 kW.
[0099] Example 5
[0100] This embodiment provides a sand-textured powder coating. The raw material ratio and preparation process are the same as those in Embodiment 1, except that the fluorine-free sand-textured agent is a composite micropowder of PMMA and nano-silicon dioxide.
[0101] The preparation process of composite micropowder includes the following steps:
[0102] A: According to mass, 100 parts of methyl methacrylate, 20 parts of dispersant, and 8 parts of initiator are mixed to obtain an oil phase mixture;
[0103] B: According to mass fraction, 100 parts of deionized water and 12 parts of stabilizer are mixed to obtain an aqueous phase mixture;
[0104] C: mixing the oil phase mixture and the water phase mixture, emulsifying and dispersing to obtain a reaction solution;
[0105] D: Add 25 parts of nano-silicon dioxide to the reaction solution; heat to 80°C while performing ultrasonic dispersion, and react for 8 hours to obtain a composite emulsion;
[0106] E: The composite emulsion is washed and dried in sequence to obtain composite micropowder of nano-silicon dioxide.
[0107] The initiator is benzoyl peroxide; the dispersant is polymethylsiloxane; and the stabilizer is a mixture of polyvinyl alcohol and polyvinyl pyrrolidone (mass ratio 1:1).
[0108] The ultrasonic frequency of ultrasonic dispersion is 320 kHz, and the ultrasonic power is 1.2 kW.
[0109] Example 6
[0110] This embodiment provides a sand-textured powder coating. The raw material ratio and preparation process are the same as those in Embodiment 1, except that the fluorine-free sand-textured agent is a composite micropowder of PMMA and nano-silicon dioxide.
[0111] The preparation process of composite micropowder includes the following steps:
[0112] A: According to mass, 100 parts of methyl methacrylate, 30 parts of dispersant, and 10 parts of initiator are mixed to obtain an oil phase mixture;
[0113] B: According to mass fraction, 120 parts of deionized water and 17 parts of stabilizer are mixed to obtain an aqueous phase mixture;
[0114] C: mixing the oil phase mixture and the water phase mixture, emulsifying and dispersing to obtain a reaction solution;
[0115] D: Add 30 parts of nano-silicon dioxide to the reaction solution; heat to 120°C while performing ultrasonic dispersion, and react for 12 hours to obtain a composite emulsion;
[0116] E: The composite emulsion is washed and dried in sequence to obtain composite micropowder of nano-silicon dioxide.
[0117] The initiator is benzoyl peroxide; the dispersant is polymethylsiloxane; and the stabilizer is a mixture of polyvinyl alcohol and polyvinyl pyrrolidone (mass ratio 1:1).
[0118] The ultrasonic frequency of ultrasonic dispersion is 350 kHz, and the ultrasonic power is 1.5 kW.
[0119] Comparative Example 1
[0120] This comparative example provides a sand-textured powder coating. The raw material ratio and preparation process are the same as those in Example 1, except that the fluorine-free sand-textured agent is PMMA micropowder that is not grafted with acrylic acid.
[0121] The sand-textured powder coatings provided in Examples 1-6 and Comparative Example 1 were subjected to performance tests.
[0122] The coating is sprayed onto the surface of the workpiece using an electrostatic spraying process, and the process parameters are controlled as follows: voltage: 60kV, working temperature: room temperature, spraying distance: 200mm, powder output: 15kg / h.
[0123] The wear resistance of the workpiece was tested using a paper tape wear tester. The results are shown in Table 1.
[0124] Table 1
[0125]
[0126]
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a fluorine-free sand graining agent, characterized in that: The following steps are involved: S11: Activate the surface of PMMA powder using low-temperature plasma technology; S12: dispersing the activated PMMA powder in an organic solvent to obtain a reaction solution A; dispersing the acrylic acid monomer in an organic solvent to obtain a reaction solution B; and dispersing the initiator in an organic solvent to obtain a reaction solution C; S13: Under nitrogen protection, the reaction liquid A, the reaction liquid B and the reaction liquid C are introduced into a microchannel reactor for graft copolymerization, and then washed and dried to obtain the PMMA micropowder with acrylic acid grafted on the surface.
2. The method for preparing the fluorine-free sand graining agent according to claim 1, characterized in that: The organic solvent is selected from any one of chloroform, dichloromethane, n-hexane and tetrahydrofuran; the initiator is selected from any one of ammonium persulfate and azobisisobutyronitrile.
3. The method for preparing the fluorine-free sand graining agent according to claim 1, characterized in that: In step S11, the particle size of PMMA powder is 10 μm-50 μm.
4. The fluorine-free sand graining agent according to claim 1, characterized in that: The flow rate of the reaction solution A is controlled to be 1-2 mL / min, and the mass fraction of the activated PMMA powder in the reaction solution A is 1-5%; and / or The flow rate of the reaction solution B is controlled to be 0.9-2.2 mL / min, and the mass fraction of the acrylic acid monomer in the reaction solution B is 15-17%; and / or The flow rate of the reaction liquid C is controlled to be 0.9-2.2 mL / min, and the mass fraction of the initiator in the reaction liquid C is 0.13-0.17%.
5. The fluorine-free sand graining agent according to claim 1, characterized in that: In step S13, the reaction temperature of the microchannel reactor is controlled to be 60-70°C.
6. The fluorine-free sand graining agent according to claim 1, characterized in that: In step S11, the PMMA powder is a composite powder of PMMA and nano-silicon dioxide.
7. A sand-textured powder coating, characterized in that: The raw materials include by weight: 80-100 parts of resin base material; 2.5-3 parts of the fluorine-free sand graining agent as described in any one of claims 1-5; 6-10 parts of alcohol dispersant; Curing agent 5-12 parts.
8. The sand-textured powder coating according to claim 7, characterized in that: The resin base material is selected from at least one of acrylic resin, polyurethane resin, epoxy resin and polyester resin; the alcohol dispersant is selected from at least one of methanol, ethanol, isopropanol, n-butanol, isobutanol, pentanol, hexanol and cyclohexanol.
9. The method for preparing a sand-textured powder coating according to claim 7 or 8, characterized in that: The following steps are involved: S21: obtaining a resin base material, a fluorine-free sand graining agent, an alcohol dispersant, and a curing agent according to their mass, and mixing and crushing them to obtain a premix; S22: Extruding the premix through a twin-screw extruder, wherein the heating temperature of the twin-screw extruder is controlled at 80-120° C., and then cooling, tableting, crushing and grinding are performed in sequence to obtain a sand-textured powder coating, wherein the equivalent particle size D50 of the sand-textured powder coating is 20-45 μm.
10. A workpiece, characterized in that: The surface of the workpiece is sprayed with the sand-textured powder coating as claimed in claim 7 or 8.
Citation Information
Patent Citations
Reflective film component and preparation method thereof
CN112358701A
Water-based full-matte finishing varnish with surface transparent textures and preparation method of water-based full-matte finishing varnish
CN117210049A
Cited By
Fluorine-free sand streak agent as well as preparation method and application thereof
CN121293412A
Fluorine-free sand-texturing agent, preparation method and application thereof
CN121293412B